Controle de Fusarium verticillioides em milho por Paenibacillus polymyxa - Marins, Mikaely Sousa (2021)
The association of Fusarium verticillioides with maize is virtually constant, but can turn to be undesired when the fungus causes disease in the crop or produces mycotoxins in the grains. The beneficial action of Paenibacillus polymyxa as an agent of biological control or as a colonizer of the rhizosphere promoting plant growth is well documented in the literature. The objectives of this study were to evaluate the potential of P. polymyxa in reducing infection of F. verticillioides in maize and to follow th e production of defense enzymes by the plant in response to infection. We used a bacterial strain previously selected from a collection, with a proven ability to inhibit the growth of F. verticillioides in axenic culture. In a field experiment, the effect of P. polymyxa application on the infection rate of maize kernel s was evaluated. In another experiment, carried out in a greenhouse, we evaluated the incidence and severity of stalk rot of maize after inoculation with F. verticillioides and different treatments with P. polymyxa. In this experiment, we also evaluated the production of plant defense enzymes phenylalanine ammonia- lyase (PAL) and glutathione reductase (GR) in maize plants, inoculated with the fungus and the antagonistic bact eria. Application of P. polymyxa reduced the incidence of Fusarium by 16% in plants naturally infected and 25% in inoculated plants. Spraying plants with P. polymyxa in greenhouse reduced the severity of stalk rot by 33% compared to the control, and increased the activity of GR enzyme. The seed microbiolization reduced the severity of stalk rot by 18%. The results obtained in this study open the perspective to developing a technique for biological control of infection caused by F. verticillioides in maize, and strategy less dependence on chemical pesticide applications.